Antibacterial activities of centrifugally spun polyethylene oxide/silver composite nanofibers. (17th February 2021) - Hasan, Md Toukir; Gonzalez, Ramiro; Chipara, Mircea; Materon, Luis; Parsons, Jason; Alcoutlabi, Mataz
Abstract: Composite nanofibers were prepared successfully by centrifugal spinning of poly(ethylene oxide) aqueous solutions containing silver nanoparticles. The core focus of the present work is to carefully evaluate the antibacterial activity of poly(ethylene oxide)–Ag composite nanofibers in the presence of Escherichia coli ( E. coli ) and Bacillus cereus ( B. cereus ) bacteria. Centrifugally spun nanofibers were obtained from poly(ethylene oxide)–Ag precursor solutions with different Ag nanoparticle loadings. The process parameters such as the spinneret rotational speed, collector‐spinneret distance, and relative humidity were optimized to obtain fine fibers. The complex morphology and flexible structure of the poly(ethylene oxide)–Ag composite fibers were investigated by scanning electron microscopy, X‐ray diffraction, energy‐dispersive X‐ray spectroscopy, thermogravimetric analysis, and Raman spectroscopy. The composite nanofibers have been proven as a strong antibacterial agent against E. coli and B. cereus due to their capacity to form superior inhibition zones. The efficiency of inhibiting bacteria by nanofibers was over 98%. The workability of the bacteria was impeded by the nanofibrous membrane as the Ag nanoparticles presented an effective chemical ability to dysfunction the bacterial structure at the nanoscale. These results demonstrate that the centrifugally spun poly(ethylene oxide)–Ag nanofibers are promising antibacterial agents for biomedical applications.